Children of persons deprived of voting rights in rural areas of Western Siberia during the process of restoring voting rights (on the example of the districts of Novosibirsk and Tomsk regions) - A. A. Kozhaeva (Омский научный вестник: Серия "Общество. История. Современность")
The Constitution of the Russian Soviet Federative Socialist Republic adopted on July 10, 1918 at the V All-Russian Congress of Soviets, defined seven categories of persons who were denied voting rights. Over time, however, the campaign of deprivation of voting right became more stringent and expanded due to the appearance of new categories. This article focuses on the analysis of petitions for the restoration of rights for one of the most prevalent groups of socially disadvantaged people, namely, the children of individuals denied voting rights. The study uses archival documents from four rural regions in Western Siberia as a basis. Using a range of ego documents, the strategies employed by children of the persons deprived of voting rights in their petitions. These strategies can be divided into four groups based on their approach: 1) children who refused to communicate with their parents; 2) children who justified their parents’ actions but don’t support them; 3) children who actively defended their parents; 4) children who considered discrimination against their entire family to be justified. The author of the article highlights the significant role of labor descriptions and loyalty demonstrations towards the Soviet government in petitions submitted by children of persons deprived of voting rights.